Three Essays on the Effects of Appraisal, Cultural, Emotional, and Cognitive Factors on Information Technologies Acceptance and Use - (:unkn) unknown (My University, 2016)
In essay 1, we propose a model, which utilized Lazarus and Folkman’s Cognitive Appraisal Theory of Emotion or Appraisal Theory (1984, 1987) as a structural foundation to lay out the nomological relationships among a person’s personal, cognitive, and emotional factors in predicting technology use behaviors. Emotion, likes many social and psychological factors, is challenging to give a full-consensus definition, and has been treated as a polar counterpart of cognition. Lazarus and Folkman’s Appraisal Theory suggested that when a person is facing a (disruptive) event, he or she appraises the possible outcomes (we suppose that appraising is a form of cognitive process), and based on the appraisal and along with other cognitive responses, together they influence his or her emotions. Both cognitive and emotional responses impact his or her behavioral intentions and behaviors. Derived from Appraisal Theory, various emotion theories and models, and TAM, we built a research model, which would provide and prove and the interplayed relationships among external, cognitive, and emotional variables. This study tested our research model in the context of four different technologies (Microsoft Access, iPad, SAP, and smartphone). The findings will provide substantial evidence of the imperative impact of emotions on technology use research and practices. In essay 2, built on the previous research model and supported by the theoretical background from essay 1, we would like to see how culture impacts on this model. Research has shown that people from different cultures do not think or behave alike. A person’s behavioral intentions and behaviors are often derived from his/her belief system. Lazarus and Folkman (1984) stated that “beliefs are personally formed or culturally shared cognitive configurations” (p. 63). They implied that the differences in culture may cause the variances while using a behavioral model (e.g. TAM) to predict or explain behaviors. In Lazarus and Folkman’s Appraisal Theory (1984, 1987), they regarded that beliefs determine what fact is, that is, “how things are” in the environment, and how they shape the understanding of its meaning” (Lazarus and Folkman, 1984, p. 63). In other words, they believed that culture and personal factors shape a person’s understanding of his/her surrounding environment. Bem (1970) distinguishes two levels of beliefs, primitive and higher-order. Primitive beliefs reside in a subconscious state within a person; when those beliefs are needed, they will emerge under specific circumstances. “Higher-order beliefs are learned” (Lazarus and Folkman 1984, p. 64) from experiences and over time become personal primitive beliefs. Often beliefs are operating underneath a person’s explicit awareness; nevertheless, beliefs could shape a person’s perceptions. We added cultural constructs to the proposed model, which were derived from Hofstede’s four cultural dimensions (individualism/collectivism, power distance, uncertainty avoidance, and masculinity/femininity), to examine the effect of cross cultural differences. In addition, the added constructs should demonstrate notable influences on a person’s cognition and emotion, and ultimately his/her technology use. In essay 3, uncertainty adversely impels one’s logical judgments, decisions, and behaviors (Baker, Bloom, Davis, 2015: Bloom, 2009; Denis and Kannan, 2013). Straube, Mentzel, and Miltner (2007) described anticipatory anxiety using “waiting for spiders” as a metaphor. Anticipatory anxiety was described that humans will estimate a possible future threat, danger, or other upcoming potentially negative events, which cause him/her anxiety (Barlow, 2000; Barlow, Chorpita, and Turovsky, 1996; Behnke and Sawyer, 2000). Research in user technology acceptance and use should not ignore uncertainty’s impact on a person’s perception and behaviors. The present study is aimed at investigating how users would feel along with what they would think, and how they would act, given an ambiguous event when the office workers are given a new technology or information system to use in their workplace. We also explore another factor, anticipatory anxiety, which is induced by uncertainty. Together, we believe that uncertainty factors and anticipatory anxiety factor would be the antecedents on user’s behavioral intention. The contribution of this study will shed light on discovering and solving knowledge in a user’s predicament in using new enterprise software, and thus enhance a better understanding for professionals when implementing it.
Keywords: Appraisal; Cognition; Culture; Emotions; ERP; TAM